The prognostic value of thyroid gland invasion in locally advanced laryngeal cancers. (1st September 2021) - Aslıer, Mustafa; Uçurum, Bahar Ezgi; Kaya, Hilmi Cem; Coskun, Hakan
Abstract: Background: Locally advanced laryngeal cancers can spread to the thyroid gland by direct invasion of cricothyroid membrane. The prevalence of thyroid gland invasion (TGI) and the predictive factors of TGI were well described in literature. However, the association of TGI with survival was undetermined yet. Objectives: The aim of this study is to analyze the effects of TGI on survival rates in patients with locally advanced laryngeal cancer. Materials and methods: Medical records of 91 patients who underwent total laryngectomy with thyroidectomy were retrospectively reviewed. Demographical, clinical, and histopathological characteristics of the patients were noted. Kaplan-Meier test was used for survival analysis. Results: Histopathology reports revealed the prevalence of TGI as 14.3% (13/91). Survival analyses showed that TGI did not affect recurrence free ( p  = .078) and overall ( p  = .080) survival rates. Conclusions: Thyroid gland invasion is one of the characteristic features of locally aggressive laryngeal tumors. In this study, TGI is not a statistically significant prognostic factor that has impact on survival of the patients with locally advanced laryngeal cancer.